Clinical and surgical outcome in patients with cervical spondylodiscitis—a single-center retrospective case series of 24 patients - Motov, S.; Stemmer, B.; Krauss, P.; Bonk, M. N.; Wolfert, C.; Steininger, K.; Shiban, E.; Sommer, B. (Frontiers in Surgery, 2024)
Cervical spondylodiscitis is an uncommon entity, with an incidence of 0.5 to 2.5 per 100.000 population, which is potentially extremely harmful. This type of infection might cause a high rate of neurological impairment in up to 29% of patients. Radical surgical debridement of the infected segment, fusion and an intravenous antibiotic regimen remain the gold standard in most spine centers. We aimed to analyze the surgical outcome in a tertiary spine center based on disease severity In this study, we retrospectively included all patients suffering from cervical spondylodiscitis between 01/2017 and 05/2022, treated at the university hospital of Augsburg. Baseline parameters on clinical presentation with symptoms, laboratory parameters, radiological appearance, and surgical parameters such as type of approach and implant as well as neurological and radiological outcomes were collected and analyzed. Descriptive statistics were performed using SPSS, and relevant correlations were examined using the t-test for independent samples and the Chi-square test.Twenty-four patients (9%) with cervical spondylodiscitis were identified. Twenty-two (92%) surgically treated patients were subdivided into complicated (n=14, 64%) and uncomplicated discitis (n=8, 36%). Seventeen patients (71%) suffered from sepsis on admission, 17 patients (71%) were diagnosed with epidural abscess on primary imaging and 5 patients (21%) had more than one discitis lesion at a distant spinal segment. The presence of epidural abscess was significantly associated with systemic sepsis (OR=6.2; p=0.03) and myelopathy symptoms (OR= 14.4; p=0.00). The most frequently detected specimen was a multisensitive staphylococcus aureus (10 patients, 42%). A total of 6 patients (25%) died after a median of 20 days despite antibiogram-accurate therapy, 5 of whom were diagnosed with a complicated type of discitis. The follow-up data of 15 patients (63%) was available with evidence of permanent neurological damage in 9 patients (38%). The surgical approach was a significant factor for revision surgery (p=0.008) as 3 of 5 (60%) ventrodorsally cases with complicated discitis were revised. Cervical spondylodiscitis presents a severe infectious disease that despite adequate surgical and antibiotic treatment, is often associated with permanent neurological damage or a fatal outcome. Complicated types of discitis might have a more challenging surgical and clinical course.